Bancarización en las instituciones no bancarias en la región Loreto, periodo 2016 - 2020 - Flores Alegria, Cristofher (2022)
The research work Banking in non-banking institutions in the Loreto region, period 2016 - 2020, aims to analyze the banking index in non-banking institutions in the Loreto region, period 2016 -2020, the research is applied and Descriptive level and non-experimental design, the population is made up of all statistical records related to deposits and credits of clients of non-banking institutions in the Loreto region in the period 2016-2020, and published by the Central Bank of Reserve, Iquitos branch and the regional GDP published by the National Institute of Statistics and Informatics. The research concludes that the bankarization rates of deposits on average are a little more than 2% and in loans their average is close to 4%. One of the explanations for this behavior is the geographic condition of the region; In addition, the credits or placements in all the years of study are higher than the collection of deposits and the Municipal Savings and Loans Banks are the most representative of the Sector.